DEVELOPMENT OF OEE (OVERALL EQUIPMENT EFFECTIVENESS) DATA PROCESSING AND REPORTING SYSTEM AS IMPROVEMENT OF OEE VALUE MONITORING PROCESS OF LIQUID FILLING MACHINE AT PT X - Anisa Maisyara, Yuyu
The competitiveness of a manufacturing industry company is determined by an effective production method with minimum waste (lean production). Overall Equipment Effectiveness (OEE) and the six big losses are methods that can be used to assess the effectiveness of using a machine. Many companies perform manual OEE monitoring with the disadvantage of being inefficient and less accurate. It is PT X that monitors OEE and six big losses manually using a worksheet for liquid dosage filling machines. This study aims to develop an OEE data processing and reporting system for liquid dosage filling machines that can improve the OEE monitoring process at PT X. The system development is carried out using a prototyping method based on the results of business analysis and user needs. Analysis of business and user needs is carried out based on the results of collecting literature data, interviews, and direct observations on the liquid filling line at PT X. System development begins with rapid system design based on user needs, then prototype and system coding by programmers. The system is tested by verifying the data entry into the form in system. The validity of the system calculation results is carried out by comparing the results of manual calculations to the results of system calculations using OEE data for January 2022. OEE monitoring using the developed system has the potential to increase the efficiency of PT X's monthly OEE monitoring process by facilitating the process of data entry, data processing and reports that are automatically generated. The system provides valid results for the calculation of OEE and six big losses with a calculation difference of 0. This system is different from several OEE calculation systems developed in other studies because it can calculate six big losses and is specific for liquid dosage filling machines at PT X. From This research, it is concluded that the developed system can increase the efficiency of the monthly OEE monitoring process of the liquid dosage filling machine at PT X up to 48.8%.